The MicAB Two-Component Signaling System Is Involved in Virulence of Streptococcus pneumoniae - Kadioglu, Aras (American Society for Microbiology, 2003)
In Streptococcus pneumoniae, the two-component signaling system MicAB was previously shown to contribute to repression of competence when oxygen is limited. In virulent strains expressing the serotype 2 and 6 capsule, mutation of the MicB kinase reduced the lag period of growth when cultures were switched from an aerobic to anaerobic atmosphere. After intranasal challenge of mice, the micB::km mutation decreased virulence, as shown by the absence of symptoms and by a lower level of recovery of CFU from lungs and blood. It is proposed that MicAB is involved in the adaptive response of the bacteria to changes in oxygen level during the course of infection.